2016
DOI: 10.21595/jve.2016.17040
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection of pipeline multiple cracks using piezoceramic transducers

Abstract: Abstract.To study the feasibility of detecting pipeline multi-cracks damage using piezoceramic transducers, the electromechanical impedance method and the stress wave based active sensing method were used respectively to perform the damage detection of pipeline with multi-cracks. In this research, the lead zirconate titanate (PZT) type transducers were used due to its strong piezoelectric effect and low cost. During the experiments, two artificial cracks on the pipeline specimen were created, ranging from 0 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Currently, the structural health monitoring technology has become a research focus [65][66][67]. The piezoceramic transducers are one of the most studied monitoring technologies [68,69], which can achieve the real-time monitoring of slurry compaction [70], internal microstructures [71] and interface debonding problems [72,73]. Considering the advantages of the piezoceramic transducer, the real-time monitoring based on it for DS-FRC members will be targeted in future research work, including the internal compactness, internal damage properties and interface debonding properties between fiber and matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the structural health monitoring technology has become a research focus [65][66][67]. The piezoceramic transducers are one of the most studied monitoring technologies [68,69], which can achieve the real-time monitoring of slurry compaction [70], internal microstructures [71] and interface debonding problems [72,73]. Considering the advantages of the piezoceramic transducer, the real-time monitoring based on it for DS-FRC members will be targeted in future research work, including the internal compactness, internal damage properties and interface debonding properties between fiber and matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The loading rate is 0.5%, and the strain ratio is −1(εmax/εmin = −1). In order to study the effect of the loading strain amplitude on the Welding material sampling 30 10 20 57 66 57 20 10 6 117 117 20 Gauge length…”
Section: Test Proceduresmentioning
confidence: 99%
“…In this condition, the welds under cyclic are prone to damage accumulation, which is observed to be a process that can cause immediate failure when the load is not large enough [13]. It should be pointed out that damage accumulation has such an important impact on the performance and service life of structure [14][15][16][17][18][19], and even several studies have focused on the damage detection of the construction structure and material [20][21][22][23][24], but there is little consideration of the weld damage accumulation in the study of seismic performance of steel tubular truss structure joints [25][26][27][28], and the difference of the constitutive relation between the welding material and base metal is often neglected. For instance, the research results of Wang [29] revealed that the welding material and its parent material of 304 L steel have different hardening laws and damage evolution laws under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…The serious structural damages of buried pipelines caused by rockfalls attracted much attention from engineers and researchers in recent years. In addition, with the recent rapid development of damage detection and structural health monitoring technology [5][6][7], the monitoring technology of buried pipelines was also developed and it plays an important role in the safe operation of pipeline network systems. In order to further analyze the damage mechanism of buried pipelines, it is necessary to conduct experimental and numerical studies on the strain behavior of buried pipelines subjected to impact loads for the safe operation of pipelines, as well as for loss prevention and environmental protection.…”
Section: Introductionmentioning
confidence: 99%